Amino acid racemization in mono-specific foraminifera from Quaternary deep-sea sediments - Kaufman, D.; Cooper, K.; Behl, R.; Billups, K.; Bright, J.; Gardner, K.; Hearty, P.; Jakobsson, M.; Mendes, I.; O'Leary, Michael; Polyak, L.; Rasmussen, T.; et al. (Elsevier BV, 2013)
The deep-sea environment is among the most stable on Earth, making it well suited for amino acid geochronology. Foraminifera with calcareous tests are distributed across the World Ocean and are often recovered in sufficient abundance from sediment cores to derive robust mean amino acid D/L values of multiple replicates from each stratigraphic level. The extent of racemization (D/L) can be compared with independent age control, which in most cases is based on correlation with global marine oxygen-isotope stages and radiocarbon ages from the same stratigraphic levels. In this study, we report the results of amino acid racemization analysis of multiple foraminifera species from well-dated sediment cores taken from the Pacific, Atlantic, and Arctic oceans. The composite of results analyzed to date (179 samples, each composed of an average of 8.6 subsamples = 1531 analyses) show that D/L values generally increase systematically down core, and are similar for samples of comparable ages from different deep-sea sites. Previously published equations that relate D/L values of aspartic and glutamic acids to post-depositional temperature and sample age for Pulleniatina obliquiloculata generally conform to the D/L trends for species analyzed in this study. Laboratory heating experiments were used to quantify the difference in the rate of racemization between P. obliquiloculata and other taxa. For example, aspartic acid in P. obliquiloculata racemizes an average of 12-16% faster than in the common high-latitude species, Neogloboquadrina pachyderma (s). Apparently, the unexpectedly high D/L values previously reported for N. pachyderma (s) older than 35 ka from the Arctic Ocean cannot be attributed to taxonomic effects. © 2012 Elsevier B.V.